Mutations in the SAC1 gene suppress defects in yeast Golgi and yeast actin function (The Rockefeller University Press, 1989)
The budding mode of Saccharomyces cerevisiae cell growth demands that a high degree of secretory polarity be established and directed toward the emerging bud. We report here our demonstration that mutations in SAC1, a gene identified by virtue of its allele-specific genetic interactions with yeast actin defects, were also capable of suppressing sec14 lethalities associated with yeast Golgi defects. Moreover, these sac1 suppressor properties also extended to sec6 and sec9 secretory vesicle defects. The genetic data are consistent with the notion that SAC1p modulates both secretory pathway and actin cytoskeleton function. On this basis, we suggest that SAC1p may represent one aspect of the mechanism whereby secretory and cytoskeletal activities are coordinated, so that proper spatial regulation of secretion might be achieved.